Elmina (Bulletin KNOB, 1989)
Elmina is a West-African town situated at the Gulf of Guinea. Because of her very favourable situation with respect to trade at the end of the 15th century the at that time small fishing-village raised the interest of European powers. These contacts determined the development and in an important measure also the character of the town. The castle Sao Jorge da Mina, which was built by the Portuguese near the village hereby played a central role.From 1637 to 1872 the castle was Dutch headquarters at the Goldcoast and the village developed into an important commercial town. At the beginning of the 19th century, after the abolition of slavery, the building lost its function of trading post. A good century later, in 1921, also the town lost her trading function because of a by the harbour promulgated trading prohibition. The town fell back on her original source of income, fishery.On the one hand this decline had the advantage that the valuable character of the town has not been affected by new or extended functions. On the other hand decay threatens to undermine this character. Only new economic impulses like improved fishery-techniques can oppose this decay of the town. But also promotion of tourism has to be thought of. Restoration of the in Elmina situated socio- and architectural historical very valuable castle St. George could be an important first step.Students in restoration-techniques from the Technical University Delft examined the possibilities for its redestination. Not the castle itself, but the environment causes problems at obtaining a tourist function. Besides problems mostly are not architectural. Therefore research has to be extended to other disciplines. This interdisciplinary research has to produce a proposal that describes how new economic impulses can rehabilitate Elmina's valuable elements and structure.